Mechanical Properties of Self-Healing Carbon Fiber-Epoxy Composite Stitched with Mendable Polymer Fiber. Issue 3 (March 2014) - Yang, T.; Du, Y.; Li, Z.M.; Wang, C.H.
Carbon fiber composites are self-healed by advance embedding of repairing agents in the composites. However, the repairing agent will influence the mechanical properties of the carbon fiber composites. In this study, poly(ethylene-co-methacrylic acid) (EMAA) filaments were stitched into carbon fiber-epoxy laminates to create a three-dimensional (3D) self-healing fiber system. Specimens with unmodified and self-healing laminates were manufactured. The mechanical properties of the carbon fiber-epoxy composite stitched with mendable polymer fiber for self-healing and unmodified laminates were compared experimentally. Results from the double cantilever beam test revealed that the stitched EMAA fibers increased the mode I interlaminar fracture toughness of the laminate by ∼120%. However, short-beam shear (SBS) strength of the composite laminates with the healing agents was slightly degraded, with a 37% reduction in the average SBS strength. The compressive-after-impact assessment showed that the strength was reduced by 6.6%. C-Scan revealed the 3D inter-connected self-healing EMAA network within the composite laminates.